The spiral of plastic pollution: a compensatory urge from the collective unconscious for an ecological‐psychological transformation of civilization - Bucher, Susanna (Journal of analytical psychology, 2022)
This article explores the symbolism of plastic pollution. Plastic and microplastic particles are now found everywhere – in the Arctic, in deep ocean trenches, in human organs – and plastic accumulates in our oceans forming gigantic spiral‐shaped garbage patches. Both spiral symbolism and E.A. Poe’s ‘Maelström’ are suggestive of a necessary fundamental ecological‐psychological transformation of our one‐sidedly logos‐dominated civilization. Plastic, the author argues, has become a carrier of our longing for immortality: in plastic, humanity has synthesized an ‘immortal’, a virtually non‐biodegradable substance. To avert what Jung called a ‘catastrophic enantiodromia’, humanity must relinquish its ecologically and psychologically detrimental consumerist mentality and jump into the unknown towards a less resource‐intensive lifestyle. The author’s dream about sea salt and spiral‐shaped marine animals is interpreted as a compensatory urge from the collective unconscious for humanity to reconnect to inner and outer nature by cultivating the neglected eros principle – feeling‐based relatedness – as a felt realization that we are part of nature on which we depend. Instead of succumbing to paralyzing fear or denial, the author argues for facing the abyss of our ecological‐psychological crisis and acting, informed by science. For ecological‐psychological transformation, Jungian psychology can play an important role. Cet article explore le symbolisme de la pollution par le plastique. Le plastique et les particules de micro‐plastique se retrouvent maintenant partout – dans l’Arctique, dans les fosses profondes des océans, dans les organes humains. Le plastique s’accumule dans nos océans formant de gigantesques vortex de déchets. Le symbolisme de la spirale et le ‘Maelström’ d’Edgar Alan Poe évoquent une transformation éco‐psychologique nécessaire et fondamentale de notre civilisation biaisée par la domination du logos. L’auteur soutient que le plastique est devenu porteur de notre désir nostalgique d’immortalité: avec le plastique l’humanité a synthétisé une substance ‘immortelle’, quasiment non‐biodégradable. Pour éviter ce que Jung appelle ‘l’énantiodromie catastrophique’, nous devons en tant qu’humanité abandonner notre mentalité consumériste qui est nuisible écologiquement et psychologiquement, et faire le saut dans l’inconnu vers un style de vie moins exigeant en ressources. Un rêve de l’auteur sur le sel marin et des animaux marins en forme de spirale est interprété en tant que mouvement compensatoire de l’inconscient collectif pour que l’humanité retrouve le lien avec la nature intérieure et extérieure en cultivant le principe négligé de l’éros – familiarité fondée sur l’émotion – comme réalisation ressentie que nous faisons partie de la nature dont nous dépendons. Plutôt que de succomber à une peur paralysante ou au déni, l’auteur propose de faire face au gouffre de notre crise écologique‐psychologique et d’agir éclairé par la science. Pour une transformation écologique‐psychologique, la psychologie Jungienne peut jouer un rôle important. Dieser Artikel untersucht die Symbolik der Verschmutzung durch Plastik. Plastik‐ und Mikroplastikpartikel sind mittlerweile überall zu finden – in der Arktis, in tiefen Meeresgräben, in menschlichen Organen – und Plastik sammelt sich in unseren Ozeanen und bildet riesige spiralförmige Müllflecken. Sowohl die Spiralsymbolik als auch E.A. Poes ‘Maelström’ legen eine notwendige grundlegende ökologisch‐psychologische Transformation unserer einseitig logosdominierten Zivilisation nahe. Plastik, so argumentiert die Autorin, sei zu einem Träger unserer Sehnsucht nach Unsterblichkeit geworden: In Kunststoff habe die Menschheit eine ‘unsterbliche’, eine praktisch nicht biologisch abbaubare Substanz synthetisiert. Um das abzuwenden, was Jung eine ‘katastrophale Enantiodromie’ nannte, muß die Menschheit ihre ökologisch und psychologisch schädliche Konsummentalität aufgeben und ins Unbekannte zu einem weniger ressourcenintensiven Lebensstil springen. Der Traum der Autorin von Meersalz und spiralförmigen Meerestieren wird als kompensatorischer Drang des kollektiven Unbewußten für die Menschheit interpretiert, sich wieder mit der inneren und äußeren Natur zu verbinden, und zwar durch das vernachlässigte Eros‐Prinzip – gefühlsbasierte Verbundenheit – als gefühlte Erkenntnis, daß wir ein Teil der Natur sind, von der wir abhängig sind. Anstatt in lähmende Angst oder Verleugnung zu verfallen, plädiert die Autorin dafür, sich den Abgründen unserer ökologisch‐psychologischen Krise zu stellen und wissenschaftlich informiert zu handeln. Für die ökologisch‐psychologische Transformation kann die Jungsche Psychologie eine wichtige Rolle spielen. Questo articolo esplora il simbolismo dell’inquinamento plastico. Le particelle di plastica e microplastica si trovano ormai ovunque ‐ nell’Artico, nelle fosse oceaniche profonde, negli organi umani ‐ e la plastica si accumula nei nostri oceani delle gigantesche chiazze di immondizia a forma di spirale. Sia il simbolismo della spirale che il “Maelström” di E.A. Poe suggeriscono una trasformazione ecologico‐psicologica necessaria e fondamentale della nostra civiltà unilateralmente dominata dal logos. La plastica, sostiene l’Autrice, è diventata un vettore del nostro desiderio di immortalità: nella plastica, l’umanità ha sintetizzato un ‘immortale’, una sostanza praticamente non biodegradabile. Per evitare quella che Jung ha definito una “enantiodromia catastrofica”, l’umanità deve abbandonare la sua mentalità consumistica ecologicamente e psicologicamente dannosa e saltare nell’ignoto verso uno stile di vita meno dispendioso in termini di risorse. Il sogno dell’Autrice sul sale marino e sugli animali marini a forma di spirale è interpretato come un impulso compensatorio dell’inconscio collettivo affinché l’umanità si ricolleghi alla natura interiore ed esteriore coltivando il principio trascurato dell'eros ‐della relazionalità fondata sui sentimenti‐ come una consapevolezza percepita di essere parte della natura da cui dipendiamo. Invece di soccombere alla paura e alla negazione paralizzante, l’Autrice sostiene di dover affrontare l’abisso della nostra crisi ecologico‐psicologica e di agire in base alla scienza. Per la trasformazione ecologico‐psicologica, la psicologia junghiana può svolgere un ruolo importante. В статье рассматривается символический смысл загрязнения пластиком. Частицы пластика и микропластика сегодня встречаются повсюду – в Арктике, в глубоких океанских впадинах, в человеческих органах; пластик скапливается в океанах, образуя гигантские спиралевидные мусорные пятна. Как символизм спирали, так и “Маэльстрём” Э. А. По наводят на мысль о необходимости фундаментальной эколого‐психологической трансформации нашей цивилизации, в которой в одностороннем порядке доминирует логос. Пластик, считает автор, стал символом нашего стремления к бессмертию: в пластике человечество синтезировало “бессмертное”, практически не разлагающееся вещество. Чтобы предотвратить явление, которое Юнг называл “катастрофической энантиодромией”, человечество должно отказаться от экологически и психологически пагубного потребительского менталитета и отправиться в неизвестность на поиски менее ресурсоемкого образа жизни. Сновидение автора о морской соли и спиралевидных морских животных интерпретируется как компенсаторное стремление коллективного бессознательного к воссоединению человечества с внутренней и внешней природой путем развития забытого принципа эроса – связи, основанной на чувстве; через нее мы осознаем, что являемся частью природы, от которой зависим. Автор полагает, что вместо того, чтобы поддаваться парализующему страху или отрицанию, необходимо посмотреть в лицо бездне эколого‐психологического кризиса и действовать, опираясь на научные данные. Юнгианская психология может сыграть важную роль для эколого‐психологической трансформации. El presente artículo explora el simbolismo de la polución plástica. Actualmente encontramos partículas plásticas y micro plásticas en todos lados – en el Ártico, en las fosas oceánicas profundas, en órganos humanos – y plásticos acumulados en nuestros océanos formando manchones de residuos gigantes de forma espiralada. Tanto el simbolismo de la espiral, como el ‘Maelström’ de E.A. Poe sugieren una transformación ecológica‐psicológica fundamental de nuestra civilización unilateralmente dominada por el logos. La autora argumenta que el plástico se ha vuelto una expresión de nuestro anhelo de inmortalidad: en el plástico, la humanidad ha sintetizado una sustancia virtualmente no‐biodegradable, ‘inmortal’. Para evitar lo que Jung ha denominado una ‘enantiodromía catastrófica’, la humanidad debe renunciar a nuestra mentalidad consumista ecológica y psicológicamente perjudicial y dar un salto a lo desconocido hacia un estilo de vida con menos recursos. El sueño de la autora sobre sal marina y animales espiralados es interpretado como el deseo compensatorio del inconsciente colectivo de que la humanidad reconecte con la naturaleza interna y externa, cultivando el descuidado principio de eros – el relacionamiento basado en el sentimiento – como una realización sentida de ser parte de la naturaleza de la cual dependemos. En lugar de sucumbir al miedo o a la negación paralizante, la autora sostiene la necesidad de confrontar el abismo de nuestra crisis ecológica‐psicológica y actuar científicamente. La psicología Junguiana puede tener una función importante en la transformación ecológica‐psicológica. 这篇文章探讨了塑料污染的象征意义。现在, 塑料和微塑料颗粒随处可见‐‐在北极, 在深海海沟, 在人体器官中‐‐塑料在我们的海洋中积累, 形成巨大的螺旋形垃圾区。螺旋形的象征意义和E.A. Poe的作品“漩涡”都暗示了我们片面理性所主导的文明必须要进行根本性的生态‐心理转变。作者认为, 塑料已经成为我们对不朽的渴望的载体:在塑料中, 人类已经合成了一种 "不朽", 一种几乎不可降解的物质。为了避免发生荣格所说的 "灾难性的物极必反", 人类必须放弃我们在生态和心理上有害的消费主义心态, 跳进未知的领域, 走向资源密集度较低的生活方式。作者关于海盐和螺旋形海洋动物的梦被解释为来自集体无意识的补偿性冲动, 从而重新达成与内在和外在的自然的联系, 通过培养被忽视的爱洛斯原则‐‐基于感觉的关联性‐‐把它作为被觉知的一部分, 即我们是我们所依赖的自然的一部分。作者没有屈服于麻痹的恐惧或否认, 而是主张面对我们的生态‐心理危机的深渊, 在科学的指导下采取行动。对于生态‐心理的转化, 荣格心理学可以发挥重要的作用